1994
DOI: 10.1007/bf00167078
|View full text |Cite
|
Sign up to set email alerts
|

Structure, diversity, and evolution of the T-cell receptor VB gene repertoire in primates

Abstract: AB T-cell receptors (TCR) that recognize major histocompatibility complex (MHC)/peptide antigen complexes regulate humoral and cellular arms of the adaptive immune response. Antigen binding sites of MHC and immunoglobulin heavy chain variable regions (Igh-V) are subject to diversity enhancing selection. We sought to establish whether positive Darwinian selection has driven diversity of TCRBV chains in the primate lineage by sequencing rearranged TCR from rhesus monkeys and chimpanzees and comparing them with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…A previous study evaluating TCR evolution between primate species found similar results for the comparison of TCR sequences between Rhesus macaques and humans, with lower rates of synonymous and nonsynonymous mutations in framework compared with CDR regions of the TCR (21). In that study, a similar analysis comparing chimpanzee to human TCR sequences did not find significant differences in mutation rates of framework and CDR regions between species.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…A previous study evaluating TCR evolution between primate species found similar results for the comparison of TCR sequences between Rhesus macaques and humans, with lower rates of synonymous and nonsynonymous mutations in framework compared with CDR regions of the TCR (21). In that study, a similar analysis comparing chimpanzee to human TCR sequences did not find significant differences in mutation rates of framework and CDR regions between species.…”
Section: Discussionsupporting
confidence: 68%
“…In addition to the highly similar structure of the TCRBV repertoire between species (i.e., the same number and similar size of TCRBV families) there was also a high degree of similarity between the individual genes, with a substantial proportion of genes having identical amino acid sequences as described before for the BV4-1 (BV7S1) gene (21). This high degree of phylogenetic relationship has led to the conclusion that the TCR repertoire as observed in humans and chimpanzees might be highly optimized, leaving little room for extensive genetic variation (20 -22).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Hence the interspecies diversity of TRGV9 sequences is smaller than the intraspecies differences of other TRGV gene segments (34). The observation that TCR chain gene segments of nonhuman primates cluster in phylogenetic analyses according to family membership instead of species designations has been also described for TCR ␣-and ␤-chain gene segments (35)(36)(37)(38)(39)(40). The high evolutionary conservation of TRGV9 sequences during more than 50 million years in conjunction with the conserved features of TCR rearrangements found in V␥9V␦2 T cells responding to IPP suggests that these cells represent an evolutionary conserved immune surveillance system.…”
Section: Discussionmentioning
confidence: 94%
“…32 (HCV is hepatotropic and replicates efficiently in chimpanzees-and the genotype 1 strain, HCV-1, typically establishes chronic infection. Exceptionally for an animal model of human disease, chimpanzees share with humans orthologous MHC 51,52 and TCR 53,54 genes.) This study revealed that a multispecific, intrahepatic CD8 ϩ CTL response during early infection correlated with HCV-1 clearance.…”
Section: Cell-mediated Immunitymentioning
confidence: 99%